Defense Downsizing: The Economic Impacts in New England - Kodrzycki, Yolanda (Maine Policy Review, 1994)
Yoland R. Kodrzycki reviews the extent of New England’s dependency on defense and various measures of the severity of defense downsizing. The analysis is put in the broader context of the New England economy. Because the economy can provide opportunities or constraints, it is important to understand the general economic environment when designing a defense conversion strategy. This article is excerpted from the author’s remarks at a conference entitled “From Defense to Offense: Converting Maine’s Economy in a Time of Shrinking Military Expenditures,” which took place in Portland on June 13, 1994. The views expressed do not necessarily reflect official positions of the Federal Reserve Bank of Boston.
Keywords: Maine; defense conversion; New England